(untitled) (Biological Sciences - PJSIR, 2003)
Latex was collected by incising the stem of E.caducifolia plant which contains 26.90 - 28.60% solid material. The chemical composition of solid material shows resinous mass 68.30 - 72.70%, where as rubber hydrocarbon is around 6.20 - 7.60 and inorganic matters lie in the range 19.00 - 22.90% and 1.50 - 1.90%, respectively. The rubber hydrocarbon was characterised by different chemical and instrumental methods. Iodine value of hydrocarbon (310.91 - 350.80%) percentage of unsaturation (83.40 - 94.10%), elemental analysis (C = 87.48 - 88.04%, H = 11.20 - 11.82%), solubility, IR spectrum (840 cm-1), 1H-NMR spectrum (olefinic proton at 5.15 - 5.20%), 13C-NMR spectrum (olefinic region 120 - 140 ppm), molecular weight (15275 - 88405), the value of Tg (- 63.02 - 60.81°C), refractive index (1.49200 to 1.49325) and specific gravity (0.93102 to 0.93628) identify rubber hydrocarbon as polyisoprene. The material is sticky and poor in strength and burning gives a smoky flame.